UPAYA MENINGKATKAN HASIL BELAJAR SISWA DENGAN MODEL PEMBELAJARAN KONTEKSTUAL PADA SISWA SMA NEGERI 1 MAUPONGGO - Melkior Wewe; Apliana Tamo Inya (Jurnal Ilmiah Mandalika Education (MADU), 2024)
This research aims to improve student learning outcomes at SMA Negeri 1 Mauponggo through the application of a contextual learning model. The contextual learning model is expected to help students relate learning material to everyday life, thereby increasing their understanding and motivation to learn. The method used in this research is classroom action research (PTK) which consists of two cycles. Each cycle includes planning, implementation, observation, and reflection. The research results show that the application of the contextual learning model can improve student learning outcomes significantly. The average student score before implementing this model was 65, and after the first cycle it increased to 75, and in the second cycle it reached 85. Apart from that, student participation in the learning process also increased, where students were more active in interacting and discussing in class. The contextual learning model is effective in improving student learning outcomes at SMA Negeri 1 Mauponggo. Therefore, it is recommended that teachers apply this model in the learning process to improve the quality of education in schools.